In Virtual Travel Communities, to examine an extended model of the theory of planned behavior used to explain how identified factors to affect co-creation intentions - LI, LI (2019)
With dramatic improvements in technologies, there is an increasing number of scholars and practitioners studying value co-creation between customers and firms. Within the Chinese context of virtual travel communities (VTCs), value co-creation between firms and customers is mainly manifest in the VTC. This article examines the factors that driving members to participate in value co-creation in the VTC and construct a theoretical model that can be seen as an extension of the theory of planned behavior (TPB). These factors have been identified as perceived VTC quality, learning motives, social integrative motives, personal integrative motives, and hedonic motives. The examination of the extended TPB model used 211 valid responses from those respondents who have performed co-creation behaviors in the VTC. The results of the structural equation model provided strong support of the extended model, indicating that these influencing factors shown above can be viewed as antecedents of attitude towards co-creation and perceived behavioral control in the VTC respectively. Both scientific and practical implications are shown explicitly below.